„Modernizacja” małżeństwa – ewolucja czy rewolucja? - Kryński, Marcin Józef (Civitas et Lex, 2023)
The aim of the article is to analyze the transformation of marriage in the context of socio-cultural changes taking place at the beginning of the 21st century. Taking up this issue is important not only for cognitive reasons, but also for social ones. At present, in many cultural circles, the principle of Christian marital morality is presented in a distorting mirror. Many attempts are made to impose on whole communities and even entire societies a model that proclaims itself "progressive" and "modern". Formerly concealed violence, molestation, mental torment, and even infanticide are coming to light. Homosexual marriages, homo and heterosexual partnerships are introduced, patchwork families are popularized, and divorces and life without commitments are completely normalized. For this reason, every attempt to reflect and search for “the right way" certainly brings us closer to finding the true essence and pattern of a harmonious and spiritual marriage created on the basis of a humanistic approach to human existence.